Review and gap analysis on mathematical programming models for urban e-grocery delivery - Basir, Nur Hazimah; Shuib, Adibah (Universiti Teknologi MARA, 2025)
Online grocery shopping or e-grocery has becoming more relevant nowadays when consumers' shopping habit changed due to pandemic COVID-19 while e-Commerce rapidly transformed consumers’ lifestyle and buying behaviour in recent years, Consumers’ expectation for faster, better and cheaper delivery put e-grocers under rising pressure to improve delivery speed, achieving environmentally friendly delivery methods and addressing issues of making profit. There have been studies worldwide on development of more efficient e-grocery delivery system. However, studies concerning e-grocery delivery in Malaysia are still lacking especially on those utilizing mathematical programming models for delivery optimization. Our study focuses on the formulation of mixed integer goal programming (MIGP) models for vehicle routing problem with time windows for homogeneous and heterogeneous fleet of vehicles. This paper presents a structured review of past studies and gap analysis on some selected mathematical programming models. The review and gap analysis provide vital information on main characteristics for models of our study. Results presented would be useful for studies that concern with finding optimal solutions, innovative approaches and the most practical techniques for urban e-grocery deliveries. These strategies could lead to time and costs savings and enhance the effectiveness and efficiency of delivery operations that benefits both e-grocers and consumers.